The Organization of the General Meeting of Shareholders based on Court Determination from the Perspective of Shareholder Rights’ Protection - Sufiarina Sufiarina; Yetti Yetti; Sri Wahyuni; M. Wira Utama (Faculty of Law, Universitas Padjadjaran, 2022)
The General Meeting of Shareholders (GMS) is generally the authority of the Board of Directors. Prior to the GMS, the Board of Directors usually invites shareholders to the GMS. In addition, the Commissioners and shareholders under certain conditions have the right to request the GMS. It is even possible for shareholders to hold a GMS based on a court order. For this reason, this study elaborates on the mechanism to hold a GMS based on a court order. This study also explores the characteristics of the procedural law in court and the holding of the GMS based on a court decision. This study employed a normative juridical method with a statutory approach, especially on Article 79 and Article 80 of the Indonesian Law on Company, and provisions of procedural law, especially civil procedural law relating to the application of the principle of audi et alteram partem. The results show that court decisions have special characteristics related to the requirements and implementation of procedural law. The court’s product in the form of a decision does not provide a balanced position regarding the right to take legal action.DOI: https://doi.org/10.22304/pjih.v9n2.a2